2011
DOI: 10.1186/ar3528
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tissue injury in lupus nephritis

Abstract: Systemic lupus erythematosus is a prototypic autoimmune disease characterized by autoantibody production and immune complex formation/deposition in target organs such as the kidney. Resultant local inflammation then leads to organ damage. Nephritis, a major cause of morbidity and mortality in patients with lupus, occurs in approximately 50% of lupus patients. In the present review, we provide an overview of the current research and knowledge concerning mechanisms of renal injury in both lupus-prone mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 97 publications
3
121
0
2
Order By: Relevance
“…70 T cells can induce tissue injury by recruiting macrophages and dendritic cells, and producing cytokines. 75 In this study, we found that neutrophils, monocytes/macrophages, and T cells are all recruited into the superficial retina after axonal injury. With flow cytometric analysis, our data show that myeloid cells are the major leukocyte subtype that infiltrate into the retina after axonal injury.…”
Section: Discussionmentioning
confidence: 58%
“…70 T cells can induce tissue injury by recruiting macrophages and dendritic cells, and producing cytokines. 75 In this study, we found that neutrophils, monocytes/macrophages, and T cells are all recruited into the superficial retina after axonal injury. With flow cytometric analysis, our data show that myeloid cells are the major leukocyte subtype that infiltrate into the retina after axonal injury.…”
Section: Discussionmentioning
confidence: 58%
“…Complement activation, and engagement of fragment crystallisable receptor and complement receptors, such as complement receptor 1, are associated with certain SLE clinical lesions such as glomerulonephritis. 25 The aetiology of SLE is thought to be multifactorial, and includes environmental and genetic factors. Compared with Caucasians, the prevalence of SLE is higher among North American Indians, African-Americans, African-Caribbeans, Hispanics and Asians.…”
Section: Sle In Indigenous Australiansmentioning
confidence: 99%
“…Together, these findings reinforce the importance of CD8 T cells in the pathogenesis of lupus nephritis. Nevertheless, discrepancies still exist in assessing the contribution of CD4 versus CD8 T cells to glomerular injury and IC deposition (22)(23)(24)(25). Thus, we wished to better clarify the role of CD8 T cells in this pathology.…”
mentioning
confidence: 99%